Jarisch-Herxheimer reaction in a patient with neurosyphilis. Issue 7 (July 1994) - Zifko, U; Lindner, K; Wimberger, D; Volc, B; Grisold, W
Abstract : A 40 year old man presented with progressive personality changes in the previous six months. Specific serological tests for syphilis in blood and CSF were highly positive and CSF sedimentation showed signs of an inflammatory process. Ten hours after the start of penicillin treatment a severe symptomatic Jarisch-Herxheimer reaction with alteration of level of consciousness, pupillary changes, and focal neurological signs developed. Jarisch-Herxheimer reaction may occur in various settings, particularly in the treatment of syphilis. Investigation of CSF before the treatment may predict a potential risk. Corticosteroid treatment has been suggested for prevention.